(untitled) (Journal of Philosophy, Culture and Political Science, 2024)
The purpose of the study is to determine the relationship between the concept of «insan kamil» (a perfect man) and the concept of «mind» in the Words of Edification of Abai Kunanbaev. Particular attention is paid to the religious and philosophical aspects of «insan kamil» in Islam, and the views of thinkers who analyzed it. Various versions of «insan kamil» are listed and the features of its appearance are con sidered, including the essence of the ontological and anthropological concepts of Ibn Arabi, Al-Ghazali, Khoja Akhmet Yassawi, in particular, their teachings on the role of man, being and mind. The study showed the compatibility of categories based on symbolism in the Words of Edification of Abai, including the concepts of «mind» and «a wise person», with the characteristics and interpretations of a perfect person. In the course of this study, information was collected regarding the theoretical basis of this topic, and it made it possible, through comparative historical, diachronic and synchronic data analysis, to determine the general views of thinkers around the concept of «mind.» In the course of the study, religious and anthropological ideas and concepts in words of edification, the scientific and philosophical function of the mind, various ethical issues that reveal the existence of a perfect person are considered, the problem of the relationship between action and intention, and the significance of spiritual existence are determined. The practical significance of the study lies in the fact that the results of the study can be used to identify the issue of the relationship between the concept of «insan kamil» among Islamic thinkers and the concept of «mind» by Abai in the subject areas of the his tory of philosophy and religious studies. Key words: Insan Kamil, Islam, ontology, Ibn Arabi, al-Ghazali, Khoja Akhmet Yassawi, Abai, mind, a wise person, words of edification.